PROFIL SOCIAL CAPITAL SUATU KAJIAN LITERATUR - Ghazali Syamni (Jurnal Bisnis dan Ekonomi, 2010)
Issues of human resources are still in the spotlight for an organization to still live in the eraof 21st century. The objectives the conceptual paper is explaining social capital profile. WorldBank, 2003, social capital is defined as institutions, social relations, networks, honesty,establishment of norms of quality and quantity of social interaction with the community. Akdere,2005 made in three forms of social capital, are; macro level, messo and micro levels level. Socialcapital at the macro level is measures of social capital which is used on a wider scope. At thislevel include the use of social capital, such as government, civil enforcement of legal certainty,Social capital at the messo level is described as a structural perspective in which social networkcapital and resources are structured to flow along the network. The micro-level social capitalemphasizes the individual's ability to mobilize resources through a local network institutions suchas social organization based on kinship. Many experts emphasized the micro level in anorganization related to the recognition, cooperation and collaboration, solidarity, loyality,reputation and access to information.Keywords: social capital, macro level, micro level , meso level, return